The Peculiar Relationship: Contemporary Anglo-French Defence Cooperation - Magill, Peter (2022)
The purpose of this thesis is to identify the current status of contemporary Anglo-French defence cooperation and consider its relevance to British defence policy. To do so it provides an overview of both existing literature on Anglo-French relations and the historical background of the relationship. It also considers several international relations theories which are relevant to the relationship. To further its analysis it considers three case studies, those being the Lancaster House Treaty, the 2011 intervention in Libya and Brexit. The thesis concludes that defence cooperation with France is of vital importance to the UK, but the relationship has been imperilled by Brexit.